2006
DOI: 10.1095/biolreprod.105.047324
|View full text |Cite
|
Sign up to set email alerts
|

Serine Peptidase HTRA3 Is Closely Associated with Human Placental Development and Is Elevated in Pregnancy Serum1

Abstract: HTRA3 is a newly identified serine peptidase of the mammalian HTRA (high-temperature requirement factor A) family, that is upregulated dramatically during mouse placental development. The current study determined whether HTRA3 was involved in human placentation. During the menstrual cycle, HTRA3 was expressed primarily in the endometrial glands, being significantly upregulated toward the mid- to late secretory phases; prominent expression in the stroma detected only in the decidual cells in the late secretory … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
56
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 55 publications
(61 citation statements)
references
References 33 publications
5
56
0
Order By: Relevance
“…However, the highest level of HtrA1 expression was found in the human placenta, suggesting that HtrA1 may play important roles in placental formation and function (Nie et al, 2003a). Our recent studies demonstrated that HtrA1 was, indeed, tightly regulated during placentation in the mouse (Nie et al, 2005), and that its closely related family member, HtrA3, is also strongly associated with placental development both in the mouse and human (Nie et al, 2003b(Nie et al, , 2006a.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…However, the highest level of HtrA1 expression was found in the human placenta, suggesting that HtrA1 may play important roles in placental formation and function (Nie et al, 2003a). Our recent studies demonstrated that HtrA1 was, indeed, tightly regulated during placentation in the mouse (Nie et al, 2005), and that its closely related family member, HtrA3, is also strongly associated with placental development both in the mouse and human (Nie et al, 2003b(Nie et al, , 2006a.…”
Section: Introductionmentioning
confidence: 93%
“…Total RNA was isolated and Northern analysis (15 g/lane) performed as previously published (Nie et al, 2006a). RNA extracted from first-trimester placenta (n ϭ 4) and decidua (n ϭ 4) were examined individually.…”
Section: Rna Extraction and Northern Blot Analysismentioning
confidence: 99%
“…This dynamic expression of HtrA3 in the placenta throughout gestation was reflected by a similar change in its maternal serum concentrations. HtrA3 concentrations were higher in pregnant women than in non-pregnant women, and the highest concentrations were measured during the first trimester [10]. In the 13th-14th week of pregnancy, increased concentrations of HtrA3 were found in the sera of women who later developed preeclampsia compared to those who had a normal pregnancy.…”
Section: Importance Of Htra3 During Early Pregnancymentioning
confidence: 85%
“…The villous syncytiotrophoblast, the distal region of the trophoblast cell columns, and the endovascular extravillous trophoblasts strongly stained for HtrA3. While its decidual expression was maintained during gestation, placental expression of HtrA3 was down-regulated during the second and third trimesters, when it was only detectable in the syncytiotrophoblast [10]. This dynamic expression of HtrA3 in the placenta throughout gestation was reflected by a similar change in its maternal serum concentrations.…”
Section: Importance Of Htra3 During Early Pregnancymentioning
confidence: 93%
See 1 more Smart Citation